Shore to Shore: How Europe's New Data Privacy Laws Help Global Libraries and Patrons. Issue 3 (3rd July 2018) - Ayala, Daniel
Abstract: As the European Union's General Data Protection Regulation (GDPR) comes into effect to ensure the data protection and privacy of the personal information of its citizens, positive benefits will also befall users around the world. By using GDPR-compliant technology systems and underlying operating processes, global users of many technology systems, including library systems, will notice improved transparency on data collection, its use and sharing, greater access and control over their own personal information, and reduced notification time when a data breach does occur involving their information. Libraries can use these changes as an opportunity to educate patrons and users on privacy topics.